2012
DOI: 10.1021/nl302069q
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Super-Resolution DNA Imaging for Genetic Analysis

Abstract: Many types of cancer and neurodegenerative diseases are caused by abnormalities and variations in the genome. We have designed a high-resolution imaging technique with high throughput and low cost for determining structural variations of genes related to genetic diseases. We initially mapped all seven nicking sites of Nb.BbvCI endonuclease enzyme on lambda DNA. Then we resolved densely labeled patterns of 107 nicking sites on human BAC DNA that is digested by Nb.BsmI and Nb.BbvCI endonuclease enzymes. This hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…These images from each color channel were than superimposed to generate a 2 color superresolved image; the mapping error in this image was 20 nm. The 2 color mapping error obtained was found to be better than 20 nm, as we and others previously reported (39,40,(43)(44)(45).…”
Section: Dual-color Acquisition and Mapping Errorsupporting
confidence: 73%
See 1 more Smart Citation
“…These images from each color channel were than superimposed to generate a 2 color superresolved image; the mapping error in this image was 20 nm. The 2 color mapping error obtained was found to be better than 20 nm, as we and others previously reported (39,40,(43)(44)(45).…”
Section: Dual-color Acquisition and Mapping Errorsupporting
confidence: 73%
“…For accurate alignment and mapping of the 2 color channels, diffraction-limited fluorescent beads were first imaged with emission spectra spanning both channels (Invitrogen). The location of the beads was matched for both channels, and a mapping matrix was generated using an IDL (Exelis Visual Information Solutions) custom mapping routine (39,40,(43)(44)(45). This mapping matrix superimposes the 2 sides of the image, each corresponding to a different color, into a 2-color image, and the images obtained were processed and analyzed using an ImageJ macro routine, which is based on the QuickPALM plugin (46).…”
Section: Dual-color Acquisition and Mapping Errormentioning
confidence: 99%
“…The importance of this problem extends beyond chemical physics, as these channel sizes form the basis for an emerging method of genomic mapping. [1][2][3] Here, the DNA is stretched by confinement in a nanochannel 4,5 and the genomic information is then read by fluorescence microscopy, either using sequencespecific probes, [6][7][8][9][10][11] the absence of fluorescence due to localized melting of AT-rich regions, 12,13 or competitive binding. 14 Genome mapping in nanochannels uses intact genomic DNA molecules that are hundreds of kilobases (and even megabases) in contour length.…”
Section: Introductionmentioning
confidence: 99%
“…Aligning these arbitrary numbers obtained from a human genome takes nearly 10, 000 hours on a sequential CPU. Moreover, research [Baday et al 2012] has shown that the resolution of the optical label method can be further enhanced by adding multiple types (colors) of labels.…”
Section: Introductionmentioning
confidence: 99%